Pharmacogenomics in pediatric leukemia. - Paugh, Steven W; Stocco, Gabriele; Evans, William E (Curr Opin Pediatr, 2010)
PURPOSE OF REVIEW: The therapeutic index of many medications, especially in children, is very narrow with substantial risk for toxicity at doses required for therapeutic effects. This is particularly relevant to cancer chemotherapy, when the risk of toxicity must be balanced against potential suboptimal (low) systemic exposure that can be less effective in patients with higher rates of drug clearance. The purpose of this review is to discuss genetic factors that lead to interpatient differences in the pharmacokinetics and pharmacodynamics of these medications. RECENT FINDINGS: Genome-wide agonistic studies of pediatric patient populations are revealing genome variations that may affect susceptibility to specific diseases and that influence the pharmacokinetic and pharmacodynamic characteristics of medications. Several genetic factors with relatively small effect may be combined in the determination of a pharmacogenomic phenotype and considering these polygenic models may be mandatory in order to predict the related drug response phenotypes. These findings have potential to yield new insights into disease pathogenesis, and lead to molecular diagnostics that can be used to optimize the treatment of childhood cancers. SUMMARY: Advances in genome technology, and their comprehensive and systematic deployment to elucidate the genomic basis of interpatient differences in drug response and disease risk, hold great promise to ultimately enhance the efficacy and reduce the toxicity of drug therapy in children.
Keywords: Antineoplastic Agents; Child; Genetic Predisposition to Disease; Genetic Testing; Humans; Individualized Medicine; Pharmacogenetics; Phenotype; Precursor Cell Lymphoblastic Leukemia-Lymphoma